Performance of Ni-W alloys as barrier film between lead free solder and copper substrate / Chew Chee Sean - Chew, Chee Sean (2011)
Due to environmental concerns, the electronics industry is actively shifting from lead solders to lead free solders. Sn based lead free solders are the most suitable 49is used in the under bump metallurgy (UBM) and substrate metallization for flip chip and ball grid array (BGA) applications. Interactions and interdiffusion between Sn based lead free solders and copper substrate result weak interface and serious reliability problems in electronic device. In order to limit the outward diffusion of copper atoms, a thin barrier layer has been used between lead free solder and copper substrate. In this study, interfacial reactions between Sn-3.5Ag (SA) and Sn-3.8Ag-0.7Cu (SAC) lead free solders and Ni-W alloy films were investigated. Ni-W alloy films with tungsten contents in the range of 5.0-18.0 at.% were prepared on copper substrate by electrodeposition in ammonia-citrate bath. Solder joints were prepared on the Ni-W coated substrate at a reflow temperature of 250oC. Multiple reflow and high temperature storage were performed on a number of samples. Spreading rate and wetting angle of solders were measured. The microstructures of the solder joints interface were investigated by field emission scanning electron microscopy. Chemical compositions of the intermetallic compounds (IMC) were analyzed by energy dispersive X-ray spectroscopy. Mechanical properties of the IMC formed were performed by nanoindentation. It was found that a Ni3Sn4 layer with faceted morphology formed between SA and the Ni-W alloy films after reflow. A ternary Sn-Ni-W was observed below the Ni3Sn4 layer. In contrast, a non-uniform (Cu,Ni)6Sn5 layer formed at interface between SAC and Ni-W alloy films. A quaternary Sn-Cu-Ni-W was found below the (Cu,Ni)6Sn5 layer. The thickness of both Ni3Sn4 and (Cu,Ni)6Sn5 layers were found to decrease with the increase of tungsten contents in the Ni-W film. The ternary Sn-Ni-W and quaternary Sn-Cu-Ni-W layers were found to be amorphous and are suggested to have formed through solid state amorphization caused by anomalously fast diffusion of Sn into Ni-W film. The hardness of each phase obtained by nanoindentation testing decreases in the following order: (Cu,Ni)6Sn5 phase > Ni3Sn4 phase > Sn-Ni-W ternary phase > Ni-18 at.% W > copper substrate > SAC solder > SA solder. The lower hardness and soft Sn- Ni-W phase is significantly related to the amorphous structure.